Using tele-emergency to avoid patient transfers in rural emergency departments: An assessment of costs and benefits. (April 2018) - Natafgi, Nabil; Shane, Dan M; Ullrich, Fred; MacKinney, A Clinton; Bell, Amanda; Ward, Marcia M
Introduction: Tele-emergency can address several challenges facing emergency departments in rural areas. The purpose of this paper is to (a) examine the rates of avoided transfers in rural emergency departments that adopted tele-emergency applications; and (b) estimate the costs and benefits of using tele-emergency to avoid transfers. Methods: Analysis is based on 9048 tele-emergency encounters generated by the Avera eEmergency programme (Sioux Falls, South Dakota) in 85 rural hospitals across seven states between October 2009–February 2014. For each non-transfer patient, physicians indicated whether the transfer was avoided because of tele-emergency activation. The cost-benefit analysis is conducted from the hospital, patient and societal perspectives, and includes technology costs, local hospital revenues and patient-associated savings. All monetary values are expressed in US$. Sensitivity analysis is conducted by examining the worst and best case scenarios of costs, revenues and savings. Results: In these analyses, 1175 avoided transfers were attributed to tele-emergency. From a rural hospital perspective, tele-emergency costs around US$1739 to avoid a single transfer. However, tele-emergency saves around US$5563 in avoided transportation and indirect patient costs. Combining these, from a societal perspective, tele-emergency has the potential to result in a net savings of US$3823 per avoided transfer while accounting for tele-emergency technology costs, hospital revenues, and patient-associated savings. Conclusion: This study highlights various stakeholder perspectives on the financial impact of tele-emergency in avoiding patient transfers in rural emergency departments. Telemedicine has the potential to reduce the number of transfers of emergency department patients and generate some revenue for rural hospitals despite associated technology costs, while incurring substantial patient savings.